Evaluation of Mouthwash Containing Citrus hystrix DC., Moringa oleifera Lam. and Azadirachta indica A. Juss. Leaf Extracts on Dental Plaque and Gingivitis - Buakaew, Watunyoo (Plants (Basel), 2021)
Oral hygiene and control of microbial plaque biofilm formation are effective methods for preventing gingivitis. Mouthwashes containing leaf extracts of the medicinal plants Citrus hystrix DC. (KL), Moringa oleifera Lam. (MO) and Azadirachta indica A. Juss. (NE) were assessed for oral healthcare and gingivitis adjunctive treatment. Three types of mouthwash were developed; KL, a combination of KL and MO (KL + MO), and a combination of KL, and NE (KL + NE). The mouthwashes were tested in vivo on 47 subjects with gingivitis who were allocated into five groups as (i) placebo, (ii) KL, (iii) KL + MO, (iv) KL + NE, and (v) 0.12% chlorhexidine gluconate (CHX). Participants were instructed to rinse with herbal mouthwash twice daily for two weeks. Gingival index (GI), plaque index (PI), and oral microbial colonies were measured at baseline and 15 days. Results showed that GI and PI of groups (ii)–(iv) significantly decreased over the placebo group, while accumulative reduction percentages of both Staphylococcus spp. and Candida spp. were found in groups (iii) and (iv). Findings indicated that the herbal mouthwashes reduced GI and PI, and showed potential as oral healthcare products.